Marketing Strategy of Islamic Higher Education Institutions: A structured-thematic analysis - M. Shohibul Aziz; Sri Hartini; Sri Gunawan (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to explore marketing strategies implemented by Islamic higher education institutions through a structured literature review method. This method was chosen to assess the extent and depth of research related to this theme. A systematic search was conducted on journal articles published in the period 2014–2023 from the Google Scholar, Emerald Insight, and Springer Link databases. The selection focused on articles from journals indexed by Scopus or Sinta and those most relevant to the research objectives. The findings indicate that although interest in marketing strategies in Islamic higher education institutions is increasing, research in this area is still in its infancy and lacks strong theoretical integration. The main strategies identified include digital marketing, promotional mix, social marketing, Islamic branding, and experiential marketing. These approaches are considered effective in attracting prospective students and strengthening institutional visibility. However, most of the reviewed studies still lack empirical validation and contextual adaptation, especially within the cultural and religious framework of Islamic education. The findings of this study provide practical insights for institutional leaders and contribute to academic discourse by highlighting emerging themes and gaps in the literature. Limitations of this study include the limited scope of the database and the lack of representation of non-English language sources. Future research needs to build a robust theoretical model and explore the application of contextual strategies to improve marketing effectiveness